Use of natural additives: seaweed oil and citrus fiber and effects marinated chicken meat - Araujo, Santiago Ruben (2025)
Omega-3 fatty acids, particularly docosahexaenoic acid (DHA), are associated with numerous health benefits. This research was conducted to evaluate the effects of DHA-rich oil from Schizochytrium sp. algae and citrus fiber as a natural alternative to sodium tripolyphosphate (STPP) in marinated chicken breast on moisture, drip loss, DHA concentration, shear force, cooking loss, microbiological analysis, and consumer sensory attributes. Five hundred sixteen chicken breast samples were treated, one group received the DHA and citrus fiber marinade, the second group was untreated (control), and a third group received a conventional marinade containing sodium chloride, sodium tripolyphosphate, and carrageenan (marinade control). Chicken enriched with the DHA and citrus fiber marinade evidenced a lower shear force than the control and conventional treatments, suggesting an improved tenderness. In addition, a significant DHA concentration of approximately 230–236 mg/100 g was achieved, and was constant even after six days of refrigerated storage. The microbiological quality remained satisfactory, with total counts of mesophilic aerobes below 3 log CFU/g and of Enterobacteriaceae and Pseudomonas spp. below 2 log CFU/g. A sensory analysis revealed no noticeable differences in taste, texture, or overall acceptability from the control, indicating a likely consumer acceptability of the enriched chicken. In conclusion, enriching chicken breasts with DHA through an injection technique offers a promising strategy to increase omega-3–fatty-acid intake, particularly for individuals with insufficient consumption of these essential polyunsaturated acids.